2015
DOI: 10.1080/00224499.2015.1089214
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Prevalence of Sexual Function Problems: The Impact of Morbidity Criteria

Abstract: Establishing the clinical significance of symptoms of sexual dysfunction is challenging. To address this, the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) introduced two new morbidity criteria (duration and symptom severity) to the existing criteria of distress. This study sought to establish the impact of these three criteria on the population prevalence of sexual function problems. The data come from a national probability survey (Natsal-3) and are based on 11,509 male a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(65 citation statements)
references
References 40 publications
3
58
0
4
Order By: Relevance
“…27 Our estimates were slightly lower than this, and decreased further when stricter morbidity criteria were used (see also ref. 28 ), and this effect has also been found in other population surveys. 24,29 Other studies do not measure dyspareunia per se, but report estimates of genital pain disorders such as vulvodynia.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…27 Our estimates were slightly lower than this, and decreased further when stricter morbidity criteria were used (see also ref. 28 ), and this effect has also been found in other population surveys. 24,29 Other studies do not measure dyspareunia per se, but report estimates of genital pain disorders such as vulvodynia.…”
Section: Discussionsupporting
confidence: 77%
“…7,8,38 Only a fraction of women affected by genital pain disorders ever receive an official diagnosis: 1.4% in a study of women meeting criteria for vulvodynia. 30 In a previous paper from Natsal-3 28 we reported that less than half of women with morbid symptoms of sexual pain had sought professional help in the last year. Among those who do seek treatment, negative experiences are common, including invalidated concerns, not receiving a formal diagnosis, and being given treatment perceived as ineffective.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this large, national probability survey of the British population aged 16 to 74 years, fewer than half of women and men with distressing sexual difficulties in the past year reported that they had sought help/advice for their sex lives during this time. This leaves the majority of those with a distressing sexual difficulty reporting that they had not sought help, demonstrating a large unmet need (Mitchell et al, 2016). Overall, there were few sociodemographic differences between those who did and did not report seeking help, particularly after taking account of age.…”
Section: Discussionmentioning
confidence: 95%
“…Preferences differed according to age, with age-35-and-over participants preferring to seek help from a general practitioner/family doctor and under-age-35 participants preferring to seek help from family/friends. This finding may reflect the types of sexual difficulties that people tend to experience at different ages (Mitchell et al, 2016), as well as younger generations being more comfortable accessing information from the Internet.…”
Section: Comparison Of Findings With Previous Researchmentioning
confidence: 93%